EVALUASI PELAKSANAAN KEGIATAN PREVENTIONOf MOTHER TO CHILD TRANSMISSION ( PMTCT ) PADA IBU HAMIL DI KOTA TANJUNGPINANG - Yuriati, Putri; Kasmini Handayani, Oktia Woro; Rustiana, Eunike Raffy (Public Health Perspective Journal, 2016)
Berdasarkan data Dinas Kesehatan Tanjungpinang jumlah ibu hamil yang melakukan skrening HIV di Puskesmas se-kota Tanjungpinang tahun 2013 jumlah 6.697 orang, yang melakukan skrening HIV sebanyak 1977. Program PMTCT ini telah berjalan sejak tahun 2008, sehingga diperlukan penguatan program baikdariefisiensi, efektifitasdan lain-lain. Tujuan penelitian ini menjelaskan UntukmengevaluasiPelaksanaan Kegiatan PMTCT Pada Ibu Hamil di Puskesmas Kota Tanjungpinang.Jenis penelitian ini deskriptif dengan metode kualitatif. Pengumpulan data menggunakan wawancara mendalam pada informan utama Kepala puskesmas , Kepala KIA, Bidan, perawat, ibu hamil, dan informan triangulasi Kepala puskesmas, Bidan Pelaksana, dan Kepala P2PL Dinas Kesehatan Kota.Hasil penelitian dalam pelaksanaan kegiatan pelaksanaan PMTCT sudah baik, hal ini terlihat dari standar input ( jumlah tenaga sudah memenuhi, tenaga kesehatan sudah terampil, fasilitas memadai, peralatan terpenuhi namun belum terkalibrasi, sudah adanya kebijakan baik dalam bentuk SOP, SK ataupun protap), standar proses ( tahap persiapan sudah baik, namun dalam pengembangan staf perlu terprogram secara pasti, pengorganisasian perlu disusun, pelaksanaan sudah berjalan sesuai dengan prosedur yang ditetapkan, Standar output (cakupankunjungan ANC meningkat, serta penularan bayi dengan HIV kecil). Diharapkan Dinas Kesehatan mengalokasikan alat pemeriksaan yang telah terkalibrasi, serta dibuatkan jadwal untuk pengembangan staf, dan untuk puskesmas tersedianya struktur organisasi kegiatan.Based on the data from Public Health CenterTanjungpinang, the number of pregnant women who went through screenings for HIV in public health centers throughout Tanjungpinang in 2013 reached up to 6697 people, 1977 of them were screened for HIV. The PMTCT has been running since 2008, so it needs more reinforcement for this program in terms of efficiency, effectiveness, and so on. The purpose of this study was to evaluate the Implementation PMTCT On Pregnant Women in Public Health Centers in Tanjungpinang. This study is a descriptive study that adopts qualitative method. Data was collected using in-depth interviews on key informants; the head of the Public Health Center, the chief of KIA (Mother and Child healthcare), midwives, nurses, pregnant women, and the triangular informants; the head of the public health center, the executive midwife, and the chief of P2PL. The results showed the implementation of PMTCT activities was good, it can be seen from the input standard (the number of health workers that already met the standard, highly skilled health workers, adequate facilities, health equipments that met the standard, however, they were not well calibrated, they already had their policies in the form of either SOP or SK ), process standard (preparation was good, however, the staff development needs to be programmed more properly, the PMTCT activity organizing was already carried out, the implementation of PMTCT activities was already underway in accordance with the established procedures, while the Standard output (increasing ANC visit coverage, and the small number of infants infected with HIV). DKK needs to allocate calibrated health screening equipments and needs to program a schedule and Public Health Centers need to create a necessary organizational structure.